ANALISIS NILAI EKONOMI PEMANFAATAN EKOSISTEM HUTAN MANGROVE DI DESA LABONE KECAMATAN LASALEPA KABUPATEN MUNA - basrudin basrudin; Lies Indriyani; Umi Putri Aningsih (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2025)
Mangrove forests play an important role in maintaining the balance of coastal ecosystems and supporting community welfare; however, their economic utilization has not been thoroughly calculated. This study aims to analyze the economic value of mangrove ecosystem utilization in Labone Village, Lasalepa Subdistrict, Muna Regency. The research was conducted from January to February 2025 using quantitative and qualitative methods. The quantitative approach was applied to calculate the economic value of mangrove utilization, while the qualitative approach was used to describe the socio-economic conditions of the community. Data were collected through observation, interviews using questionnaires, and documentation, with a total of 21 respondents consisting of 20 fishermen and 1 tourism manager (BUMDes). The results show that the direct benefits from mangrove forests, in the form of fish and crab catches, reached IDR 370,446,000/year (94%), while the indirect benefits from mangrove tracking ecotourism contributed IDR 20,832,000/year (6%). Overall, the total economic value of the mangrove ecosystem in Labone Village is IDR 391,278,000/year. These findings confirm that mangrove ecosystems provide a significant contribution to the coastal community’s economy, highlighting the need for sustainable management. Keywords: Labone Village, Mangrove Forest, Direct Use Value, Indirect Use Value, Economic Value